Teens and sex: sex education in aristocratic intellectual families of Russia in the second half of XIX – early XX centuries - Veremenko, Valentina (Przegląd Wschodnioeuropejski, 2018)
The article analyzes the approaches to sex education of children in noble-intelligent environment that were formed in Russia during the second half of XIX – early XX centuries. It is noted that on the one hand these practices reflected a certain evolution, and on the other, the earlier forms actively continued to coexist with the later ones. The theme is studied on the analysis of a wide range of sources: publicistic materials and documents of managemenzt and record keeping, works of educators and hygienists, memoirs. The traditional form of children’s sex education in a noble family, that was the most popular until the 80-ies of the XIX century, was a boycott of discussion of this topic, the fight to preserve the “innocence” of girls and consent to “training” of young men to “natural relations”. At the turn of the century an increasing number of parents came to the recognition of the need for sexual awareness in the field of sexual relations, but, not wanting to be engaged in this task, they tried to delegate it to “experts”. Finally, at the end of the period under review the overwhelming majority of educators and hygienists came to the conclusion that sex education should be a family thing. However, this professional approach found no special support in real life.